Zoltan Somhegyi: Mother Nature’s Exhibition: On The Origins Of The Aesthetics Of Contemporary Northern Landscapes - Somhegyi, Zoltán (The Nordic Journal of Aesthetics, 2017)
In this article Zoltán Somhegyi investigates the aesthetic qualities of Northern landscape representations, with a special focus on how contemporary examples are connected to classical ones. First he examines the history of the aesthetic appreciation of these sites, starting from their early modern reception and from the differentiation of “Northern” and “Mediterranean” landscapes: while the Mediterranean ones were highly valued already from the 15th–16th centuries on, the “wilder” Northern landscapes were admired mainly from Romanticism onwards. This has, among others, an aesthetichistorical reason, namely the birth of the category of the sublime; and in this case the harmonious Mediterranean landscapes and the irregular yet impressive Northern ones relate to each other as the category of beautiful does to the sublime. This is why from Romanticism on Northern landscapes became not only aesthetically valuable, but even more capable than the Southern ones to move the spectator. This is especially because, from a gnoseological point of view, the landscape might be a place – and the landscape representation a means – of self-interpretation. The historical overview is then used to better understand some of the most important characteristics of contemporary Northern landscape interpretations and representations from leading artists of the region, which are analysed in the second part of the article.